Access, quality and wellbeing in engineering Work Integrated Learning placements: Implications for equity and diversity. - Lloyd, Natalie; Paull, Megan; Male, Sally; Clerke, Teena (National Centre for Student Equity in Higher Education, Curtin University, 2019)
Access, quality and wellbeing in engineering Work Integrated Learning placements: Implications for equity and diversity is a mixed methods study which examines student engineers’ experiences in Work Integrated Learning (WIL) placements. The study provides insights into how to guide improvements in engineering WIL practice, particularly in relation to access, quality and wellbeing for students in equity groups. This report outlines the study, its methods and findings that build on knowledge and insights gained from a Systematic Literature Review (SLR) of international research studies and current debates on WIL access, quality and wellbeing, engineering-specific WIL placements and unpaid WIL. The review informed the analysis of data collected from three sources; institutional WIL placement information, student responses to a quantitative and qualitative online questionnaire, and semi-structured interviews with students about their WIL placement experiences supplemented by interviews with university staff working in WIL related programs in the four participating universities. The purpose was to examine student engineers’ narratives of their WIL placement experiences and provide insight into their perceptions of the ease or difficulty of access, degree of placement quality, contribution to or detraction from wellbeing, support or lack thereof; and students’ development of engineering professional identity.